ISLAMIC STATE’S COMMUNICATION STRATEGY IN RUSSIA AND THE UK: A COMPARATIVE STUDY OF PROBLEMS AND WAYS TO COUNTER THEM - N. V. Eremina; D. Lowe (Сравнительная политика)
Since establishing their self-proclaimed Caliphate in Syria and Iraq, Islamic State’s communications strategy has proved effective in recruiting foreign jihadist fighters and people to immigrate to the region to live, as well as radicalising people who remain in their home state to their cause. This article is a comparative study on the impact this strategy has had on Russia and UK and analyses the threat cased to both states in the recruitment of individuals to Islamic State’s cause and how their respective counter-terrorism agencies can counter this within a legal framework to ensure they operate within the rule of law. It is necessary to compare the positions of Russia and the UK since the states have different view over conflicts in Middle East, besides that Britain joined the US’ coalition. Russia has got a broader counter-terrorism legislation that is more effective being compared to the British one. At the same time the states need to combine their efforts against global Islam radicalization.